A Bibliometric Analysis and Mapping of On-Line Registration System in Hospital - Erindah Dimisyqiyani; Sedianingsih Sedianingsih; Rizky Amalia Sinulingga; Nurul Azizah (Universitas Airlangga, 2020)
This study analyzes the Bibliometric study about online registration at the hospital. This analysis includes statistical information obtained from the Scopus database of 1,456 research journals taken from 1999 to 2019. Keywords verified from the survey result are used to retrieve relevant articles from the database. The result of the study shows that the journal article occupies the top position is